MENINGKATKAN PENGELOLAAN KEUANGAN DI SEKTOR SWASTA MELALUI TEKNIK PENGANGGARAN - Junjunan, Mochammad Ilyas; Saifuddin, Muchammad; Nawangsari, Ajeng Tita; Susanto, Febry Fabian (Universitas Muhammadiyah Gresik, 2024)
Training in budgeting techniques is key to successful and sustainable financial management, both for individuals and organizations. This mentoring activity aims to provide participants with an understanding of the importance of financial management in the private sector, especially for financial directors and managers to plan and control budget-based business operations. This mentoring and training uses a method that focuses on extracting information, implementing, and monitoring evaluation based on tutorial practicum activities directly in the computer laboratory on financial management in the private sector and budgeting techniques. The results of this service show an increase in the understanding and ability of participants in preparing budget-based operational and financial plans at the Labini AMDK company, Madura. In addition, 82% of the participants' satisfaction level with the service activities carried out by the service team of the Faculty of Economics and Islamic Business at UIN Sunan Ampel Surabaya. In the future, mentoring and training activities, as well as monitoring and evaluation, can be consistently carried out with different directions and focuses according to the obstacles faced by the community so that the level of understanding and implementation of budget-based planning can continue to be developed for effective and efficient performance achievement.